Inhibitory effect and mechanism of action of juniper essential oil on gray mold in cherry tomatoes - Wu, Yu-Xuan; Zhang, Yun-Di; Li, Na; Wu, De-Dong; Li, Qi-Meng; Chen, Yun-Ze; Zhang, Guo-Cai; Yang, Jing (Frontiers in Microbiology, 2022)
Juniper essential oil (JEO), which is mostly known as an immune system booster and effective detoxifier, has substantial antimicrobial activity. A comparison of the inhibitory effects of three plant essential oils from juniper (Juniperus rigida), cedarwood (Juniperus virginiana), and cypress (Crupressus sempervirens) on four plant pathogenic fungi indicated that JEO was the most effective at inhibiting the growth of gray mold (Botrytis cinerea). Additional studies were subsequently conducted to explore the in vivo and in vitro antifungal activity and possible mechanism of JEO against B. cinerea. The results show that JEO inhibited the germination of spores and mycelial growth of B. cinerea in a concentration-dependent manner and exhibited strong inhibition when its concentration exceeded 10 μL/mL. JEO also significantly inhibited the incidence of disease and diameters of gray mold lesions on cherry tomato fruit (Solanum lycopersicum). After 12 h of treatment with JEO, the extracellular conductivity, and the contents of soluble protein, malondialdehyde, and hydrogen peroxide were 3.1, 1.2, 7.2, and 4.7 folds higher than those of the control group, respectively (P<0.05), which indicated that JEO can damage membranes. Scanning electron microscopy observations revealed that JEO affected the morphology of mycelia, causing them to shrivel, twist and distort. Furthermore, JEO significantly improved the activities of the antioxidant-related enzymes superoxide dismutase and catalase but reduced the pathogenicity-related enzymes polygalacturonase (PG), pectin lyase and endoglucanase of B. cinerea (P<0.05). In particular, PG was reduced by 93% after treatment with JEO for 12 h. Moreover, the 18 constituents of JEO were identified by GC-MS analysis, mainly limonene (15.17%), γ-terpinene (8.3%), β-myrcene (4.56%), terpinen-4-ol (24.26%), linalool (8.73%), α-terpineol (1.03%), o-cymene (8.35%) and other substances with antimicrobial activity. Therefore, JEO can be an effective alternative to prevent and control gray mold on cherry tomato fruit.